Pengaruh Pemberian Pencahayaan dan Konsentrasi Sukrosa Terhadap Pertumbuhan dan Produksi Umbi Mikro Kentang (Solanum Tuberosum L.) - Yushi Mardiana; Sumarji (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the effect of the concentration of sucrose and lighting on the growth and production of potato micro tubers. This research was conducted at the Tissue Culture Biotechnology Laboratory of PT. BISI International Tbk. The treatments given were lighting settings in the incubation room and giving different concentrations of sucrose on basic media. This study used a completely randomized design method with 5 replications. Data were analyzed with Anova and further tested with BNJ. Observation results showed that bright light and a sucrose concentration of 80 g/L gave the best results on the growth of potato plantlets aged 14 to 70 days after planting. Observation of the number of micro tubers, weight of micro tubers, and diameter of micro tubers showed that the combination of dark light treatment and a sucrose concentration of 120 g/L resulted in the highest average value